2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.325
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Social Networks To Motivate Individuals to Reduce their Ecological Footprints

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 15 publications
(11 reference statements)
0
94
0
Order By: Relevance
“…Pierce, Odom and Blevis [21], Froehlich, Findlater and Landay [11] and Pierce and Paulos [22] describe the various eco-visualization devices that have been constructed in order to make visible the flow of electrical energy and to highlight the amount of electricity consumed by a household. He and Greenberg [13], Mankoff, et al [16], and Foster, et al [9] describe the ways in which social networking systems and computer mediated communication have been used as means of supporting and motivating energy conservation and sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Pierce, Odom and Blevis [21], Froehlich, Findlater and Landay [11] and Pierce and Paulos [22] describe the various eco-visualization devices that have been constructed in order to make visible the flow of electrical energy and to highlight the amount of electricity consumed by a household. He and Greenberg [13], Mankoff, et al [16], and Foster, et al [9] describe the ways in which social networking systems and computer mediated communication have been used as means of supporting and motivating energy conservation and sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Mankoff, et al found that "strong participation in social movements is most likely when activities can be easily integrated into daily life," suggesting that integrating prosocial feedback into commonly used sites is most likely to have the greatest effect on participation [15]. Additionally, they find that taking advantage of existing social networks through popular websites can create "motivational schemes that leverage group membership."…”
Section: Related Workmentioning
confidence: 99%
“…The advancement and availability of sensing systems for environmentally related activities (e.g., human activity inference [4]) and interactive displays to feedback this data (e.g., mobile phones) provides a rich space of prospects for new types of ecofeedback solutions [5]. Currently there is an increasing number of commercial applications that provide real time energy monitoring.…”
Section: Related Workmentioning
confidence: 99%